Antimicrobial Properties of Medicinal Plants Against Staphylococcus aureus, Escherichia coli and Candida albicans Bacteria - Kipkorir, Kiptoo G.; Wanjohi, Benard; Ndegwa, John; Maina, Margaret (African Journal of Education,Science and Technology (AJEST), 2023)
Herbal medicine has been used in Africa for centuries and continues to be an important aspect of traditional medicine in many African communities. While Euclea divinorum, Carissa edulis and Prunus africana has a long history of traditional use in Kenya, more research is needed to determine its safety and efficacy for these medicinal purposes. Therefore, this study assessed the antimicrobial capabilities of Euclea divinorum Hern (Ebenaceae), Carissa edulis, and Prunus africana against Staphylococcus aureus, Escherichia coli, and Candida albicans bacteria to complement the work of other researchers. Leaves, roots and stem barks of of the three plants were purposively collected from Elgeyo Marakwet County. The samples were analyzed at University of Eldoret Biotechnology Laboratory, Kenya. The samples were ground into powder and successively extracted with hexane, methanol and acetone. Antimicrobial activity of the extracts was determined by agar disc diffusion method. After 24 hours of introducing the roots, leaves and stem bark extracts to the colonies on petri dishes, the inhibitory diameters of the wells were measured to test their antibacterial activity. The roots, leaves and stem bark extracts of E. divinorum, C. edulis and P. africana against S. aureus, E. coli, and C. albicans exhibit varying degrees of antimicrobial activities against S. aureus and E. coli bacterial strain and C. albicans fungal strain. E. divinorum and C. edulis roots extracts exhibited antimicrobial potency against S. aureus, E. coli, and C. albicans while the leaves of E. divinorum and P. africana showed antimicrobial activity against S. aureus and E. coli bacterial strain. Lastly, the methanol stem bark extract of P. africana was only active against E. coli, and C. albicans however, the stem bark extract of E. divinorum and C. edulis were not against S. aureus, E. coli, and C. albicans. It is therefore recommended that root extracts of E. divinorum and C. edulis and the stem bark extracts of P. Africana may provide potential sources for the development of alternative antibacterial agents while E. divinorum and C. edulis agents may provide potential sources for further development of antifungal agents for the treatment of diseases.